2022
DOI: 10.2351/7.0000574
|View full text |Cite
|
Sign up to set email alerts
|

Laser beam brazing of aluminum alloys in XHV-adequate atmosphere with surface deoxidation by ns-pulsed laser radiation

Abstract: Laser beam brazing is an established manufacturing process due to its low heat input and esthetically appealing seams. However, brazing of materials with high oxygen affinity, such as aluminum alloys, requires the removal of surface oxides prior to the brazing process, commonly through the application of chemical fluxes that may be harmful to the environment and to health. The approach presented here dispenses with the use of fluxes and involves oxide layer removal by means of ns-pulsed laser radiation within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 3 publications
1
6
0
Order By: Relevance
“…The results of the oxygen measurement show that XHV-adequate oxygen concentrations can locally be achieved by adding silane to the arc process zone. This is similar to earlier results in related work [ 23 , 24 ]. The spectroscopic analyses are suitable to further elaborate the mechanisms leading to the previously found oxygen reduction.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The results of the oxygen measurement show that XHV-adequate oxygen concentrations can locally be achieved by adding silane to the arc process zone. This is similar to earlier results in related work [ 23 , 24 ]. The spectroscopic analyses are suitable to further elaborate the mechanisms leading to the previously found oxygen reduction.…”
Section: Discussionsupporting
confidence: 93%
“…Considering that the natural oxide layer on aluminum is only 2 nm thick, the reduction effect achieved in the present study is more than sufficient. Previous studies already showed that when the oxide layer is removed and the joining atmosphere prevents re-oxidation, wetting of the surface is no challenge anymore, and flux-free brazing is possible [ 7 , 12 , 24 ]. This effect can be exploited for the plasma process, too.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Aman et al illustrate that laser beam brazing of aluminum alloys in an oxygen‐free atmosphere efficiently prevents reoxidation, while at the same time facilitating the removal of the oxide layer, thereby making the use of flux obsolete. [ 60 ] In their work, Aman et al used a setup of two laser beam sources, a pulsed (pw) laser beam source for removal of the oxide layer with pulses in the nanosecond regime and a continuous wave (cw) laser beam source for the brazing process. The process was performed inside a glove box, which was filled with silane‐doped argon providing an oxygen‐free atmosphere.…”
Section: Oxygen‐free Production Processesmentioning
confidence: 99%